Analisis Sosiologis tentang Keterlibatan Publik Gereja Diaspora Indonesia di Kota Oarai, Jepang: Sociological Analysis of the Public Involvement of the Indonesian Diaspora Church in Oarai City, Japan - Lycie Lea Tarore (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2025)
This study aims to describe and analyze the involvement of the Indonesian diaspora church in Oarai City, Japan, in building a process of social integration with the local community. The diaspora church serves as a spiritual and cultural center for Indonesians living abroad, but has gradually taken on a broader social role in the public life of the Oarai community. Using a descriptive qualitative approach and reviewed through the perspective of church sociology, this study examines the role of the church based on two concepts of Jurgen Moltmann, namely public theology and knowledge of other communities. Moltmann's public theology emphasizes the church's responsibility to present the values of the Kingdom of God through concrete actions in the community. The findings show that the Indonesian diaspora church actively builds relationships with Japanese churches, local governments, and the surrounding community through social activities such as cultural festivals, beach cleanups, and other community collaborations. This involvement strengthens the positive image of the Indonesian community and reduces resistance from the local community. In addition, the process of cross-cultural introduction between the Indonesian and Japanese communities opens up space for dialogue and mutual understanding. This study confirms that the public involvement of the diaspora church plays a significant role in shaping social integration and multicultural harmony in Oarai City.